"The economy of trust"? Competing grassroots economics and the mobilization of (mis-)trust in a Catalonian cooperative. (June 2023) - Bäumer Escobar, Vinzenz
Rather than theorizing trust and mistrust in the abstract, recent anthropological scholarship has shown how trust and mistrust emerge in particular social settings. In this article, I build on this scholarship by drawing on fieldwork with the members of an anti-capitalist Catalonian cooperative who looked to create alternative economic systems that were said to be based on trust. The central aim of this article is to redirect analytical attention from the emergence of the experience of (mis-)trust in particular contexts, toward an analysis of how trust and mistrust are mobilized to make particular iterations of an 'alternative economy' emerge out of competing grassroots economic conceptualizations. By analysing how trust and mistrust are constituted within a relational field involving the state and a broader landscape of cooperative movements, this article shows that socio-economic formations are continually formed through embodied, affectively charged practices instead of being solely 'based' on trust or mistrust.